The bloody country - Collier, James Lincoln 1928-; Collier, Christopher 1930- (New York Four Winds Press, 1976)
In the mid-eighteenth century a family moves from Connecticut to Pennsylvania and becomes involved in the property conflict between the two states.
Keywords: Frontier and pioneer life -- Fiction; Wyoming Valley (Pa.) -- History -- Juvenile fiction; Wyoming Valley (Pa.) -- History -- Fiction; Pennsylvania -- History -- Fiction